Intercultural sensitivity as a mediator in the relationship between implicit intercultural identification and emotional disturbance—An exploratory study of international high school students - He, Jiayin; Song, Xiaoqi; Wang, Chanyu; Zhang, Ruibin (Frontiers in Psychiatry, 2023)
Background Intercultural adaptation is always associated with emotional disturbances. Intercultural communication competence, as an important competence of intercultural adaptation, involves implicit intercultural identification and intercultural sensitivity. Competence in these areas promotes the process of intercultural adaptation. Little is known about the relationship between intercultural communication competence and emotional disturbances in new students attending international high schools. The intercultural adaptation process of this population requires attention because of the increasing number of high school students attending international schools, and the fact that most of these teenagers are immersed in intercultural contexts for the first time. Objective This study aimed to investigate the prevalence of emotional disturbance in new students in an international high school and confirm the relationship among implicit intercultural identification, intercultural sensitivity, and emotional disturbances. Methods Study 1 was an investigation of the prevalence of emotional disturbance in 105 students in their 1st year at an international high school using the Self-rating Depression Scale and Self-rating Anxiety Scale. Of these students, 34 were invited to participate in Study 2 to further explore the relationship between intercultural sensitivity, implicit intercultural identification, and emotional disturbances using the Intercultural Sensitivity Scale and Single Category Implicit Association procedure. Results Study 1 indicated that 15.24% of students were affected by apparent depression and 10.48% had anxiety symptoms. Study 2 revealed that emotional disturbances significantly correlated with intercultural sensitivity (p < 0.01) and implicit intercultural identification (p < 0.01). The openness factor from intercultural sensitivity mediated the relationship between implicit intercultural identification and depression (ratio of indirect effect = 41.04%, p < 0.05) and anxiety symptoms (ratio of indirect effect = 34.65%, p < 0.05). Conclusion The study revealed that a significant proportion of students in the 1st year of international high school are affected by emotional difficulties. However, intercultural communication competence is a protective factor. Enhancing the international communication competence of senior students in international high schools is important to mitigate mental health challenges.